THE SOCIAL SIGNIFICANCE OF FORMING PATRIOTIC MIND IN CHILDREN THROUGH POETRY (Academia Science Repository, 2023)
This article reveals the social significance of using the ideals of national heroism through poetry in the formation of the patriotic spirit in primary classes.